Program Seribu Jalan Mulus Kota Bengkulu: Analisis Strategi Infrastruktur Untuk Pembangunan Wilayah - Rikardo, Yanuar (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
The Seribu Jalan Mulus (A Thousand Smooth Roads) Program is a flagship policy of the Bengkulu City Government aimed at accelerating the development of neighborhood road infrastructure to enhance regional connectivity and improve residents’ quality of life. This study analyzes the implementation strategy of the program, identifies the challenges encountered, and evaluates its effectiveness in promoting sustainable regional development. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis focused on the implementation by the Public Works and Spatial Planning Agency (PUPR) of Bengkulu City. The findings indicate that the program has significantly improved accessibility and mobility, especially in densely populated and peripheral areas. However, the implementation faces several obstacles, including budget constraints, geographic difficulties, inconsistent construction quality, and weak interagency coordination. The analysis also shows early signs of good governance principles being applied, although impact-based evaluation remains underdeveloped. The study recommends strengthening performance-based monitoring and evaluation systems, enhancing technical capacities of field implementers, and encouraging broader involvement from communities and non-government sectors in infrastructure oversight.